In Vitro Feasibility of a Sac-Sealing Endoprosthesis in a Double Chimney Graft Configuration for Juxtarenal Aneurysm. (August 2014) - Niepoth, Wouter W.; de Bruin, Jorg L.; Lely, Rutger L.; Wisselink, Willem; de Vries, Jean-Paul P.M.; Yeung, Kak K.; Blankensteijn, Jan D.
Purpose: To investigate in an in vitro juxtarenal aneurysm flow model the feasibility and efficacy of using a sac-sealing endoprosthesis in a chimney graft configuration. Methods: In two experiments, a Nellix sac-sealing endoprosthesis was used as the main graft in a double-branched chimney graft configuration, using a self-expanding Viabahn stent-graft and a balloon-expandable Advanta V12 stent-graft in a pressurized silicone juxtarenal aneurysm flow model. In two consecutive experiments, the chimney graft balloons were inflated (1) at the beginning of and (2) to simulate varying renal ischemic times half-way through the injection of the sac-sealing polymer into the Nellix endobags. The balloons and were kept inflated until the endobags were filled and the polymer was cured. The aneurysm model was connected to a roller pump, pumping gelatin-water at a rate of 100 beats per minute. Before and after 24 hours of continuous flow, computed tomography (CT) scans were made using contrast injection. The CT scans were reconstructed and analyzed for gutter cross-sectional area, total gutter volume, chimney graft compression, and volume of space between the aneurysm wall and the endoprosthesis. Results: Differences in gutter size between both types of chimney grafts were minimal. Chimney graft compression exceeded 50% if the balloons were inflated in the chimney grafts halfway through polymer injection into the endobag. Twenty-four hours of flow did not influence chimney graft patency or gutter size. Conclusion: In a juxtarenal aneurysm flow model, we demonstrated the technical feasibility of a sac-sealing endoprosthesis in a chimney graft configuration. This early evidence suggests that balloon dilation of chimney grafts should occur over the entire period of polymer injection and curing to prevent considerable chimney graft compression.